Drug Utilization Pattern in Pneumonia among Pediatric Patients at a Tertiary Care Hospital - Yadav, Anita; Rimal, Bandana; Aryal, Anita; Paudel, Nabina (MedS Alliance Journal of Medicine and Medical Sciences, 2023)
INTRODUCTION: Pneumonia remains the leading cause of hospitalization and mortality in young children in low and middle-income countries like Nepal. Antibiotics are commonly prescribed for pediatric pneumonia patients. To prevent antimicrobial resistance, antibiotics must be prescribed rationally. Therefore, the purpose of this study was to evaluate the drug utilization pattern in pediatric pneumonia patients at a tertiary care hospital by using World Health Organization (WHO) prescribing indicators. MATERIALS AND METHODS: A descriptive cross-sectional study was conducted among pediatric pneumonia patients at Universal College of Medical Sciences, Bhairahawa, Nepal from December 2022 to May 2023. Ethical approval was taken from the Institutional Review Committee (UCMS/IRC/191/22) and the purposive sampling method was used. Data were collected from pro-forma to assess WHO prescribing indicators and analyzed in Statistical Package for Social Sciences (SPSS) version 20 program and expressed as frequency and percentage for all variables. RESULTS: A total of 1408 drugs were prescribed to 196 prescriptions or patients. The average number of drugs per prescription was 7.18. The most common 51.5% of prescriptions contain 4-5 drugs per prescription. The percentage of prescriptions with antibiotics and injections was 100% respectively. Drugs prescribed by generic name were 44.24% and those matched to the national Essential Drugs List of Nepal were 53.19%. Cephalosporins (86.7%) were the most frequently prescribed antibiotics followed by aminoglycosides (79.1%). All the antibiotics were given parenterally (100%). CONCLUSIONS: The study reported inadequate compliance with WHO prescribing indicators and recommended policy formulation and application by regulatory agencies to promote the drug utilization study.